Radiation-Induced Sarcoma of the Head and Neck Following Radiotherapy for Nasopharyngeal Carcinoma: A Single Institutional Experience and Literature Review - Lou, Jianlin; Jiang, Lin; Dai, Xinshen; Wang, Huanhuan; Yang, Jia; Guo, Liang; Fang, Meiyu; Wang, Shengye (Frontiers in Oncology, 2021)
Background and Objective: Radiotherapy (RT) is the primary treatment option for nasopharyngeal carcinoma (NPC) that is associated with radiation-induced sarcomas (RIS). This study aims to investigate clinicopathological features and Head and neck RIS prognosis after NPC RT. Methods: The medical and radiological records of the NPC patients (n=14074) referred to Zhejiang Cancer Hospital, Hang zhou, China between Junuary1995 and December 2018 were retrospectively reviewed. Among them, 22 patients were determined to have RIS after RT for NPC. The clinicopathological data, diagnosis, treatment and follow-up results of 22 patients with RIS were analyzed in this retrospective research. All 22 patients underwent surgery as the main treatment. The levels of Overall Survival (OS) were determined through the Log-rank test and Kaplan–Meier method. Results: Among these patients, 13 were males and 9 were females so that the males-to-females ratio was 1.44:1. The age during the primary RT of NPC ranged from 25 to 61 years old (median age: 37 years). Patients' ages ranged from 33 to 73 years old (median age: 52.5 years) when diagnosed RIS. The latency period for development of the RIS is between 3 to 36 years (median: 8.5 years) after RT. In this cohort, R0 resection was achieved in 13 cases, R1 resection in 5 cases and R2 resection in 4 cases. At the time of the follow-up time ranges from 2 to 102 months (median 14 months), 15 patients had died of disease. Kaplan-Meier methods resulted in that the 2-year, 3-year and 5-year cumulative OS rate was 50.3%, 43.2%, and 14.4%, respectively. The median survival time was 34 months. Surgical resection with R0 resection achieves significantly better prognosis (P=0.012). Patients under the age of 37 years old at the time of initial RT had relatively better prognosis (P=0.035). Conclusions: Albeit the incidence of RIS after RT of NPC is generally low, the treatment of RIS is very difficult. RIS are associated with poor overall prognosis. R0 resection should be regarded as the primary and optimal choice in treating with RIS and can improve prognosis.